2015
DOI: 10.2147/jpr.s83486
|View full text |Cite
|
Sign up to set email alerts
|

A particular effect of sleep, but not pain or depression, on the blood-oxygen-level dependent response during working memory tasks in patients with chronic pain

Abstract: BackgroundPatients with chronic pain (CP) are often reported to have deficits in working memory. Pain impairs working memory, but so do depression and sleep problems, which are also common in CP. Depression has been linked to changes in brain activity in CP during working memory tasks, but the effect of sleep problems on working memory performance and brain activity remains to be investigated.MethodsFifteen CP patients and 17 age-, sex-, and education-matched controls underwent blood-oxygen-level dependent (BO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 80 publications
1
4
0
Order By: Relevance
“…A recent study, using fMRI, found that although there were no differences in WM performance between the groups, insomniacs showed abnormalities in neural function, both in terms of reduced activation of task-related regions and the reduced ability to adjust activation with increasing task difficulty ( Drummond et al, 2013 ). A similar pattern has also been found among chronic pain patients, where sleep disturbances had a stronger effect than both pain and depression on the modulation of neural activity ( Elvemo et al, 2015 ). Such findings might suggest that cognitive deficiencies in insomnia are related to alterations in neural activity, rather than just being an epiphenomena of excessive sleepiness.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…A recent study, using fMRI, found that although there were no differences in WM performance between the groups, insomniacs showed abnormalities in neural function, both in terms of reduced activation of task-related regions and the reduced ability to adjust activation with increasing task difficulty ( Drummond et al, 2013 ). A similar pattern has also been found among chronic pain patients, where sleep disturbances had a stronger effect than both pain and depression on the modulation of neural activity ( Elvemo et al, 2015 ). Such findings might suggest that cognitive deficiencies in insomnia are related to alterations in neural activity, rather than just being an epiphenomena of excessive sleepiness.…”
Section: Discussionsupporting
confidence: 74%
“…Studies in this field of research are also characterized by small sample sizes ( N ≤ 25) ( Drummond et al, 2013 ; Elvemo et al, 2015 ; for a meta-analysis see Fortier-Brochu et al, 2012 ). This means that only very large effects would be statistical significant ( Button et al, 2013 ).The studies that find impairments in working memory report subtle, mild, or moderate effects ( Altena, Van Der Verf, Strijers, & Van Someren, 2008 ; Fortier-Brochu & Morin, 2014 ; Shekleton et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 51 This is interesting because there are factors coexisting with chronic pain, such as poor sleep, depression, and anxiety which can also affect cognitive performance. Alterations in brain activation and interference with attention processes after sleep deprivation have been found in earlier studies 52 , 53 and therefore measures of disturbed sleep should be taken into account in future research.…”
Section: Discussionmentioning
confidence: 83%
“…Optimal cognitive function depends on interaction within networks of brain regions. For learning, memory, and pattern separation abilities, the most central structure for normal functioning is the hippocampus [ 25 , 26 ], while executive functions, working memory and information processing speed depend on frontal and parietal cortices and their connectivity [ 27 , 28 ]. The intention was to test cognitive abilities that depend on brain regions susceptible to damage during hypoglycaemia [ 11 , 21 ] and cognitive abilities that are recognised to be impaired in patients with type 1 diabetes [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%